Characteristics of Japanese Puppet Theatre - Le, Lu Thi Thanh (VNU Journal of Foreign Studies; Vol 32 No 2, 2016)
Abstract: Puppet theatre art ( Bunraku ) emerged in Japan during the Edo period and was popularized throughout the country from the 19 th century. Bunraku was recognized by UNESCO as “Masterpiece of the Oral and Intangible Heritage of Humanity” and a “World Intangible Cultural Heritage” in 2003 and later was inscribed on UNESCO’s Representative List of the Intangible Cultural Heritage of Humanity in 2008. This art combines puppet controlling art, storytelling art and music performing art. Bunraku is a lively art which is able to present different topics of life of the Japanese people. This paper presents an account of the characteristics of Bunraku and makes some comparisons between Japanese puppet theatre and Vietnamese water puppet theatre. Keywords: Japanese studies, puppet theatre, Bunraku.